2022
DOI: 10.3390/jcm11205978
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Rheumatoid Arthritis Patients’ 2-Year Infliximab, Abatacept, and Tocilizumab Persistence Rates

Abstract: Background: Drug persistence reflects an agent’s efficacy and safety in routine practice. This study was undertaken to compare the 2-year persistence rates of three biologic disease-modifying antirheumatic drugs (bDMARDs) used to treat rheumatoid arthritis (RA) and to describe their efficacy and safety profiles. Methods: This retrospective, observational, single-center study included RA patients who had received at least one intravenous dose of infliximab, abatacept, and/or tocilizumab. Two-year drug persisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…Dos Santos et al concluded that tocilizumab, abatacept, etanercept, and golimumab had a significantly higher persistence, and infliximab showed a significantly lower persistence compared with According to real-world data, the persistence of biological agents in RA can be affected by various factors beyond efficacy and safety, including previous biological treatments, comedications, and baseline disease activity [21]. Thus, although biological treatments with different mechanisms of action have demonstrated similar efficacy in clinical trials, differences in persistence have been reported among different classes of bDMARDs in our data and previous studies [8,[17][18][19], although conflicting data also exist [22,23]. The exact reasons for this finding remain unclear; however, the pharmacological characteristics of tocilizumab can be considered a potential cause.…”
Section: Discussionsupporting
confidence: 42%
“…Dos Santos et al concluded that tocilizumab, abatacept, etanercept, and golimumab had a significantly higher persistence, and infliximab showed a significantly lower persistence compared with According to real-world data, the persistence of biological agents in RA can be affected by various factors beyond efficacy and safety, including previous biological treatments, comedications, and baseline disease activity [21]. Thus, although biological treatments with different mechanisms of action have demonstrated similar efficacy in clinical trials, differences in persistence have been reported among different classes of bDMARDs in our data and previous studies [8,[17][18][19], although conflicting data also exist [22,23]. The exact reasons for this finding remain unclear; however, the pharmacological characteristics of tocilizumab can be considered a potential cause.…”
Section: Discussionsupporting
confidence: 42%
“…En un estudio que comparaba las tasas de persistencia de infliximab, abatacept y tocilizumab, con un seguimiento de 2 años, publicado el 2022, se reportó una persistencia para tocilizumab de 73,1% al año y de 62,4% a los dos años. En este estudio se observó una tendencia no estadísticamente significativa a mejor retención de tocilizumab e infliximab que abatacept 21 .…”
Section: Datos Para Los Distintos Biológicos Incluidos En La Lrs En C...unclassified